2020
DOI: 10.1111/trf.16116
|View full text |Cite
|
Sign up to set email alerts
|

Dominant immune response to HLA‐B57/B58 molecules after platelet transfusion

Abstract: Background: Patients with hematologic malignancies require prophylactic or curative platelet transfusions to prevent or treat bleeding. Treatments such as chemotherapy, radiotherapy, and hematopoietic stem cell transplantation cause persistent thrombocytopenia, necessitating platelet transfusions. However, class I HLA antibodies can cause a serious complication: immune-mediated platelet refractoriness. The mechanisms of alloimmunization are incompletely understood. We explored the immunogenicity of HLA molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Differences in the expression of HLA‐ABC or HLA‐A2, HLA‐B7, and HLA‐B57 would indicate a difference in haplotype expression profile potentially accounting for variable immunogenicity. HLA‐B57 was not markedly more strongly expressed on the surface of the cells studied, whereas we showed, in a previous retrospective study, that a high proportion of polytransfused patients develop anti‐HLA‐B57 6 . Other HLA molecules may be overexpressed.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Differences in the expression of HLA‐ABC or HLA‐A2, HLA‐B7, and HLA‐B57 would indicate a difference in haplotype expression profile potentially accounting for variable immunogenicity. HLA‐B57 was not markedly more strongly expressed on the surface of the cells studied, whereas we showed, in a previous retrospective study, that a high proportion of polytransfused patients develop anti‐HLA‐B57 6 . Other HLA molecules may be overexpressed.…”
Section: Discussioncontrasting
confidence: 53%
“…HLA-B57 was not markedly more strongly expressed on the surface of the cells studied, whereas we showed, in a previous retrospective study, that a high proportion of polytransfused patients develop anti-HLA-B57. 6 Other HLA molecules may be overexpressed. Significant interindividual variation was observed for HLA-B8, -B12, and -B35 expression on the surface of PLTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested this hypothesis by determining the levels of CD27 + MPs in PCs. CD27 plays an important role in the regulation of CD4 + TL responses and CD4 + functions during alloimmunization ( 25 27 ). We therefore studied the interaction of CD27-expressing MPs with CD4 + TLs and its functional effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a first study with patients with hematologic malignancies, we showed that these anti-HLA specific CD4 + T responses are present in alloimmunized patients ( 7 ). Regardless of the antigen studied, these CD4 + T-cell responses had similar, rather monofunctional profiles different from more conventional responses ( e.g.…”
Section: Introductionmentioning
confidence: 99%